RELEVANSI SEMANGAT ZELUS ANIMARUM MENURUT VINSENSIUS A PAULO BAGI KATEKIS DALAM MEWARTAKAN INJIL MASA KINI - Oktavianti Kevin; Don Bosco Karnan Ardijanto (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2026)
The main focus of the study is to examine the relevance of the spirit of zelus animarum (the spirit of saving souls) according to Vincent a Paulo for the catechists in proclaiming the Gospel of God. In the present days, the catechists have faced various challenges such as secularization, globalization, and moral crisis, and so on. In the context of those challenges, the spirit of zelus animarum experienced by Saint Vincent a Paulo becomes so relevant to the life, work and the preaching of the catechists. The study was done by using a literature study methods. Literature data was analyzed using a content analysis technique. The aims of the study were to explore the relevance of the spirit of zelus animarum for catechists to proclaim the gospel of God, and to determine how far the catechists have appreciated the spirit of zelus animarum throughout their work of service and the proclamation of the gospel of God. The results of the study indicated that the spirit of zelus animarum is an important source of strength and motivation for catechists to proclaim the Gospel of God in a more contextual and creative way in the changing society.